Effect of Drought on the Methylerythritol 4-Phosphate (MEP) Pathway in the Isoprene Emitting Conifer Picea glauca - Perreca, Erica; Rohwer, Johann; González-Cabanelas, Diego; Loreto, Francesco; Schmidt, Axel; Gershenzon, Jonathan; Wright, Louwrance Peter (Frontiers in Plant Science, 2020)
The methylerythritol 4-phosphate (MEP) pathway of isoprenoid biosynthesis produces chlorophyll side chains and compounds that function in resistance to abiotic stresses, including carotenoids, and isoprene. Thus we investigated the effects of moderate and severe drought on MEP pathway function in the conifer Picea glauca, a boreal species at risk under global warming trends. Although moderate drought treatment reduced the photosynthetic rate by over 70%, metabolic flux through the MEP pathway was reduced by only 37%. The activity of the putative rate-limiting step, 1-deoxy-D-xylulose-5-phosphate synthase (DXS), was also reduced by about 50%, supporting the key role of this enzyme in regulating pathway metabolic flux. However, under severe drought, as flux declined below detectable levels, DXS activity showed no significant decrease, indicating a much-reduced role in controlling flux under these conditions. Both MEP pathway intermediates and the MEP pathway product isoprene incorporate administered 13CO2 to high levels (75-85%) under well-watered control conditions indicating a close connection to photosynthesis. However, this incorporation declined precipitously under drought, demonstrating exploitation of alternative carbon sources. Despite the reductions in MEP pathway flux and intermediate pools, there was no detectable decline in most major MEP pathway products under drought (except for violaxanthin under moderate and severe stress and isoprene under severe stress) suggesting that the pathway is somehow buffered against this stress. The resilience of the MEP pathway under drought may be a consequence of the importance of the metabolites formed under these conditions.